Obstructing interfacial reaction between NiOx and perovskite to enable efficient and stable inverted perovskite solar cells - Zhang, Jiaqi; Long, Juan; Huang, Zengqi; Yang, Jia; Li, Xiang; Dai, Runying; Sheng, Wangping; Tan, Licheng; Chen, Yiwang (Chemical engineering journal (Lausanne, Switzerland : 1996), 2021)
[Display omitted] •The interfacial redox reaction between NiOx and perovskite is obstructed.•SaC-100 is developed as a modifier layer in NiOx-based perovskite solar cells.•SaC-100 can efficiently reduce the open-circuit voltage loss of device.•SaC-100 can inhibit perovskite decomposition ascribed from interfacial reaction. In NiOx-based perovskite solar cells (PVSCs), the interfacial redox reaction between Ni3+ (on the surface of NiOx) and A-site cation salt (MAI in perovskite precursor solution) is invariably ignored. This adverse reaction will generate PbI2-rich hole extraction barriers at the NiOx-perovskite interface, which limits hole transmission and increases charge recombination, thus resulting in open-circuit voltage (Voc) loss. Furthermore, it will accelerate perovskite degradation by deprotonating the precursor amine and oxidizing iodide to interstitial iodine, which induces the severe instability of devices. Herein, a physical separation strategy by introducing a modifier layer to obstruct the detrimental reaction is explored. The results demonstrate that the trimethylolpropane tris(2-methyl-1-aziridinepropionate) (SaC-100) depositing onto NiOx can suppress the reaction between Ni3+ and MAI to endow the improvement of conductivity and reduction of interfacial defects, thus reducing Voc loss and enhancing device stability. Moreover, the interfacial energy level alignment and the morphology of perovskite are also optimized. As a result, the PVSCs device based on NiOx/SaC-100 presents the best power conversion efficiency (PCE) of 20.21% with a superior Voc value of 1.12 V. Furthermore, the device shows better light and thermal stability because of the hindering effect and defect passivation effect of SaC-100.